Oil palm frond fibers pulp from kraft pulping process– effect of beating - R.C.L. Nasrullah; Wan Rosli Wan Daud; . Pinalty; . Adisalamun (Syiah Kuala University, 2013)
The main objective of this research is to determine the effect of beating to physical, mechanical and optical properties of the paper. The pulp that is used in this research is pulp from Oil Palm Frond (OPF). Pulping method that was carried out in this research is the kraft pulping which was undergo in 4 different conditions (20% NaOH: 20% Na2S; 20% NaOH, 30% Na2S; 30% NaOH, 20% Na2S and 30% NaOH, 30% Na2S). The beating process is carried out using PFI Mill Beater and five amounts of beating were imposed to each pulp (0, 250, 500, 750 and 1500 rotations). From the result obtained, the freeness (CSF) of the pulp was decreased against the increasing amount of beating. The optimum amount of beating is at 1500 rotations for tensile strength (5981.1 N/m), bursting strength (660.72 kPa) and folding endurance (915). For tearing resistance (730.23 mN), the optimum amount of beating is at 250 rotations. Beating also contributes to reduce the brightness and the opacity too. The result show that suitable beating stage for kraft OPF pulp is at 1500 rotations, because almost all testing give optimum or closely to optimum result at this amount of beating.